The Impact of Sea Surface Temperature and Containing Chlorophyll-A on The Results of Skipjack Tuna (Katsuwonus Pelamis) Catch in The Indian Ocean Waters - Sinaga, Mardame Pangihutan; Siburian, Daniel Tony Edyt (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Oceanographic factors can be an indicator in determining the potential of fishing grounds. The sampling technique of sea surface temperature (SST) and chlorophyll-a data in this study was carried out spatially and temporal using satellite image data which can be downloaded from Aqua MODIS. This study aimed to determine variations in SST distribution and chlorophyll-a concentration in Indian Ocean waters using Aqua MODIS imagery from June 2023 to May 2024; analyzing the relationship between the distribution of SST and chlorophyll-a with the number of pelagic fish catches in the Indian Ocean waters. The type of fish used as research material is skipjack tuna (Katsuwonus pelamis). The distribution of SST in the Indian Ocean waters for June 2023-May 2024 is between 29,15-31,64 °C, where there is a significant decrease in temperature from 31,10-29,15 °C due to the east monsoon wind and the chlorophyll-a distribution is around between 0,24-0,73 mg/m³ with the highest average distribution in the western season. This phenomenon causes chlorophyll-a to increase in the western season because the frequency of rainfall in this season is sufficient, causing nutrients to increase due to vertical stirring, which can increase chlorophyll-a at the sea surface. There is no relationship between SST and chlorophyll in the number of skipjack tuna catches in transition II with a strong correlation value and a significance value (F) of 1,o, meaning that SST and chlorophyll-a on skipjack tuna to the skipjack tuna catches not influence for each season, the influence of significant event is thought to be a lag in the food chain and high rainfall. This study reveals that while variations in sea surface temperature and chlorophyll-a concentration are significant understanding oceanographic conditions, they do not directly influence skipjack tuna catch rates, suggesting that other ecological factors, such as food chain dynamics and seasonal rainfall patterns, may play a more critical role.